The effect of partial substitution of Ni by Mg on the structural, magnetic and spectroscopic properties of the double perovskite Sr2NiTeO6. Issue 36 (22nd August 2016) - Orayech, B.; Ortega-San-Martín, L.; Urcelay-Olabarria, I.; Lezama, L.; Rojo, T.; Arriortua, María I.; Igartua, J. M.
Abstract : The structural, magnetic and spectroscopic properties of the freeze-drying synthesized Sr2 Ni1− x Mg x TeO6 ( x = 0.0, 0.1, 0.2, 0.3 and 0.5) oxides are analyzed by means of X-ray and neutron powder diffraction, electron paramagnetic resonance, diffuse reflectance and magnetic susceptibility. Abstract : In this report, the structural, magnetic and spectroscopic properties of the freeze-drying synthesized Sr2 Ni1− x Mg x TeO6 ( x = 0.0, 0.1, 0.2, 0.3 and 0.5) oxides are analyzed by means of X-ray powder diffraction (XRPD) and neutron powder diffraction (NPD), electron paramagnetic resonance, diffuse reflectance and magnetic susceptibility. The XRPD and NPD data analysis using the mode-crystallography approach have revealed that at room temperature (RT), all the compositions are monoclinically distorted with the space group I 2/ m . The high and low temperature analyses have shown that these materials suffer a series of three structural phase transitions. The EPR results have shown that the spectra of all the compositions are centred at g ≈ 2.28, indicating a slightly distorted octahedral environment of Ni 2+, which is in agreement with the crystal structure analysis. The increase of the Mg 2+ content in Sr2 Ni1− x Mg x TeO6, provokes a decrease of the dipolar interaction effects and thus, the resonance becomes narrower. This resonance does not completely disappear which leads to the idea that the long-range magnetic order is not completely established when x ≥ 0.3. The substitution of the Ni 2+ ( S = 1) ions by Mg 2+ ( S = 0) ions, also induces a weakening of the antiferromagnetic interactions, which is reflected in the diminishing of the absolute value of θ and the Néel temperature T N . The magnetic structure determination revealed the existence of an antiferromagnetic coupling for x - and z -spin components of the nickel atoms.